Creative Conflict Resolution : More than 200 activities for keeping peace in the classroom (K-6) . - Kreidler, William J. (Parsippany, NJ Good Year Books, 1984)
Over 20 conflict resolution techniques with examples and more than 200 class-tested activities and games offer constructive responses to your students' problem behavior. Includes hints for resolving your own conflicts with associates.
- This book is printed on cut-out paper
- Includes bibliographical references
- Includes an activity index and a general index
- Includes some illustrations and listings in black-and-white
Keywords: Creative activities and seat work - Handbooks, manuals, etc; Classroom management - Handbooks, manuals, etc